OBTAINING THE SUITABLE TECHNIQUES FOR PALYNOLOGICAL PREPARATION - Eko Budi Lelono (Testing Center for Oil and Gas LEMIGAS, 2001)
The term of â€œstandard techniquesâ€ in preparation is no longer accepted since every sample has discrete characteristic which may require different treatment. Experiments prove that the modifications are needed to process the Eocene samples from Central Java and South Sulawesi.